Connexin Hemichannel Blockade Is Neuroprotective after Asphyxia in Preterm Fetal Sheep - Davidson, Joanne O. (Public Library of Science, 2014)
Asphyxia around the time of preterm birth is associated with neurodevelopmental disability. In this study, we tested the hypothesis that blockade of connexin hemichannels would improve recovery of brain activity and reduce cell loss after asphyxia in preterm fetal sheep. Asphyxia was induced by 25 min of complete umbilical cord occlusion in preterm fetal sheep (103–104 d gestational age). Connexin hemichannels were blocked by intracerebroventricular infusion of mimetic peptide starting 90 min after asphyxia at a concentration of 50 µM/h for one hour followed by 50 µM/24 hour for 24 hours (occlusion-peptide group, n = 6) or vehicle infusion for controls (occlusion-vehicle group, n = 7). Peptide infusion was associated with earlier recovery of electroencephalographic power after asphyxia compared to occlusion-vehicle (p<0.05), with reduced neuronal loss in the caudate and putamen (p<0.05), but not in the hippocampus. In the intragyral and periventricular white matter, peptide administration was associated with an increase in total oligodendrocyte numbers (p<0.05) and immature/mature oligodendrocytes compared to occlusion-vehicle (p<0.05), with a significant increase in proliferation (p<0.05). Connexin hemichannel blockade was neuroprotective and reduced oligodendrocyte death and improved recovery of oligodendrocyte maturation in preterm fetuses after asphyxia.